Acute effects of posture on intraocular pressure - Nelson, Emily S. (PLoS One, 2020)
Many experiments have documented the response of intraocular pressure (IOP) to postural change. External forces caused by gravitational orientation change produce a dynamic response that is encountered every day during normal activities. Tilting the body at a small downward angle is also relevant to studying the effects of hypogravity (spaceflight), including ocular changes. We examined data from 36 independent datasets from 30 articles on IOP response to postural change, representing a total population of 821 subjects (≥1173 eyes) with widely varying initial and final postures. We confirmed that IOP was well predicted by a simple quantity, namely the hydrostatic pressure at the level of the eye, although the dependence was complex (nonlinear). Our results show that posturally induced IOP change can be explained by hydrostatic forcing plus an autoregulatory contribution that is dependent on hydrostatic effects. This study represents data from thousands of IOP measurements and provides insight for future studies that consider postural change in relation to ocular physiology, intraocular pressure, ocular blood flow and aqueous humor dynamics.